The mechanical and physical properties of 3D printing filament made from recycled polypropylene and ground tyre rubber treated with alkali - Yusuf, Yusliza; Mustafa, Nuzaimah; Yusof, Yusra Fitri; Sulistyarini, Dwi Hadi (Universiti Putra Malaysia Press, 2024)
When molten, used vehicle tyres are unable to decompose or be recycled. Despite global efforts to find new uses for these materials, many worn tyres are still dumped in landfills. Therefore, this study proposes using ground tyre rubber (GTR) as a fill material for recycled polypropylene 3D printing filament. The filament composite’s physical and mechanical properties will be assessed in this investigation. GTR is expected to give the filament elastic characteristics, which could lead to rubber-like filaments. This study filled recycled polypropylene (rPP) polymer matrix composites with GTR to make filament. The mechanical and physical properties of a 3D-printed specimen made from rPP and GTR filament with varying compositions were analysed. Compared to pure rPP, rPP/GTR samples with 3 wt% GTR had a maximum tensile strength of 716.76 MPa. The flexural test findings showed that rPP/GTR with 3 wt% GTR had the highest flexural strength at 80.53 MPa, followed by rPP/1 wt% GTR at 65.38 MPa. In physical tests, the rPP/GTR at 5 wt% GTR had the highest water absorption at 5.41 %, and the wt% of GTR connected directly with water absorption. This study has shown that affordable, environmentally friendly rPP/ GTR filaments can be developed with less amount of GTR content (3 wt%) and used for 3D printing applications, helping to lessen the impact of plastic and waste while having valuable mechanical and physical properties that are comparable to those of the pure polypropylene material produced.